Evaluation Algorithm - Based on PID Controller Design for the Unstable Systems - Wan Ismail, Ibrahim; Erliza, Serri; Mohd Riduwan, Ghazali (Asian Research Publishing Network (ARPN), 2015)
PID controller consists of proportional, integral and derivatives controllers and it's widely used in industrial control system to provide optimal and excellent performance for any system. In term of controlling, unstable system exist when the system doesn’t reach a steady-state value and will instead head towards infinity. This may cause damage to the system and might bid danger in certain systems. Evaluation algorithm develops to tune the PID controller for a better performance. In this project, the evaluating PSO algorithm based on PID controller design for unstable system was proposed. Particle Swarm Optimization (PSO) is computation method by simulation of swarms behaviour in performing their tasks. In the implementation of PSO in the PID controller, the swarm will travel to search the best value of parameter Kp, Ki and Kd. In this project, the stability impact of implementation of PSO in PID controller is being investigated. This implementation offers the stability effects to the unstable system by reducing the error and provides better performance of the system.